2007
DOI: 10.1111/j.1442-9071.2007.01617.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized treatment study comparing three treatment options for chalazia: triamcinolone acetonide injections, incision and curettage and treatment with hot compresses

Abstract: To our knowledge, this is the first prospective randomized study comparing the three methods of chalazia treatment. Results suggest that a single triamcinolone acetonide injection followed by lid massage is almost as effective as incision and curettage in the treatment of chalazia and with similar patient satisfaction and less pain and patient inconvenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 15 publications
1
59
0
Order By: Relevance
“…Typically the routine incision and curettage procedure for chalazion removal results in a significant pain scale. Goawalla et al [11] documented a median pain score of 7/10 for 45 patients treated by I&C when using only subcutaneous injection of 2% lidocaine with a drop of 0.5% proxymethocaine. Buik et al [12] demonstrated a median pale scale of 6/10 for 15 patients using only local injection of 2% lidocaine with 1:10,000 adrenaline subcutaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically the routine incision and curettage procedure for chalazion removal results in a significant pain scale. Goawalla et al [11] documented a median pain score of 7/10 for 45 patients treated by I&C when using only subcutaneous injection of 2% lidocaine with a drop of 0.5% proxymethocaine. Buik et al [12] demonstrated a median pale scale of 6/10 for 15 patients using only local injection of 2% lidocaine with 1:10,000 adrenaline subcutaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a common alternative surgical procedure for chalazion removal, which has documented less pain [11,12], is intralesional or extralesional steroid injection. Complete absence of pain was documented when combing topical cutaneous anesthetic such as EMLA prior to transcutaneous injection of triamcinolone acetonide (TA) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, incision and curettage, total excision, intralesional steroid injections, and botulinum neurotoxin type A. [1][2][3] Complications of surgical drainage of the chalazion include, eyelid margin notching, trichiasis, loss of lashes, and inadvertent globe injury. 4 Incomplete chalazion drainage can result in granulation tissue prolapsing into the conjunctiva or skin.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that chalazia which did not respond to 2 or 3 injections were more likely to benefit from incision and curettage surgery. Goawalla and Lee's (2007) prospective randomized study compared the effectiveness of hot compresses, steroid injections and surgical curettage in 136 patients. They reported that steroid injections and incision and drainage surgery had comparable results, and gave better results than conservative treatment with hot compresses.…”
mentioning
confidence: 99%